2020
DOI: 10.3233/faia200547
|View full text |Cite
|
Sign up to set email alerts
|

Oversampling Based on Data Augmentation in Convolutional Neural Network for Silicon Wafer Defect Classification

Abstract: Silicon wafer defect data collected from fabrication facilities is intrinsically imbalanced because of the variable frequencies of defect types. Frequently occurring types will have more influence on the classification predictions if a model gets trained on such skewed data. A fair classifier for such imbalanced data requires a mechanism to deal with type imbalance in order to avoid biased results. This study has proposed a convolutional neural network for wafer map defect classification, employing oversamplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated the effectiveness of deep learning for silicon wafer defects [26,27] with a focus on single-type defects [28,29,30,31,32]. However, there is a need to investigate more mixed-type defects, which are becoming common with the increasing complexity of fabrication processes.…”
Section: Defect Segmentationmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of deep learning for silicon wafer defects [26,27] with a focus on single-type defects [28,29,30,31,32]. However, there is a need to investigate more mixed-type defects, which are becoming common with the increasing complexity of fabrication processes.…”
Section: Defect Segmentationmentioning
confidence: 99%
“…In this paper, geometric transformations are used on the oversampled data. One of the following geometric transformations is randomly applied on each image, rotation by (0, 90, 180, 270) and flipping horizontally or vertically [34].…”
Section: Data Preprocessingmentioning
confidence: 99%
“…To increase the quantity and diversity of the scarce training data, Kang [61] demonstrated the effectiveness of rotation-based data augmentation in wafer map pattern classification, adopting a LeNet5 like CNN. Batool et al [62] performed augmentation by rotating and flipping images for imbalance management and robust training.…”
Section: A: Custom-made Cnn For Single-label Defect Classificationmentioning
confidence: 99%